'Drawing aside the curtain': natural childbirth on screen in 1950s Britain. Issue 3 (19th September 2017) - AL-GAILANI, SALIM
Abstract: This article recovers the importance of film, and its relations to other media, in communicating the philosophies and methods of 'natural childbirth' in the post-war period. It focuses on an educational film made in South Africa around 1950 by controversial British physician Grantly Dick-Read, who had achieved international fame with bestselling books arguing that relaxation and education, not drugs, were the keys to freeing women from pain in childbirth. But he soon came to regard the 'vivid' medium of film as a more effective means of disseminating the 'truth of [his] mission' to audiences who might never have read his books. I reconstruct the history of a film that played a vital role in teaching Dick-Read's method to both the medical profession and the first generation of Western women to express their dissatisfaction with highly drugged, hospitalized maternity care. The article explains why advocates of natural childbirth such as Dick-Read became convinced of the value of film as a tool for recruiting supporters and discrediting rivals. Along the way, it offers insight into the British medical film industry and the challenges associated with producing, distributing and screening a depiction of birth considered unusually graphic for the time.